2001
DOI: 10.1117/1.1353200
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive-neighborhood histogram equalization of color images

Abstract: Histogram equalization (HE) is one of the simplest and most effective techniques for enhancing gray-level images. For color images, HE becomes a more difficult task, due to the vectorial nature of the data. We propose a new method for color image enhancement that uses two hierarchical levels of HE: global and local. In order to preserve the hue, equalization is only applied to intensities. For each pixel (called the ''seed'' when being processed) a variable-sized, variable-shaped neighborhood is determined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…The AHE algorithm enhances local image contrast by scaling pixel intensities to use the full scale of possible pixel intensities in localized regions of the image, thereby increasing contrast. AHE has been used to reveal important anatomical details in a variety of biological tissues (Buzuloiu et al 2001;Paranjape et al , 1994;), and we observed significant improvements in tracking ventral body wall movements after AHE processing. We tuned the AHE parameters using one body wall preparation, and then we used the same parameters for all the preparations because all leech body wall had similar patterning.…”
Section: Image Processing and Analysissupporting
confidence: 54%
“…The AHE algorithm enhances local image contrast by scaling pixel intensities to use the full scale of possible pixel intensities in localized regions of the image, thereby increasing contrast. AHE has been used to reveal important anatomical details in a variety of biological tissues (Buzuloiu et al 2001;Paranjape et al , 1994;), and we observed significant improvements in tracking ventral body wall movements after AHE processing. We tuned the AHE parameters using one body wall preparation, and then we used the same parameters for all the preparations because all leech body wall had similar patterning.…”
Section: Image Processing and Analysissupporting
confidence: 54%
“…Buzuloiu et al proposed a image color image scheme based on adaptive neighborhood histogram equalization [4]. The main idea of this approach is to use two levels of equalization viz.…”
Section: Introductionmentioning
confidence: 99%
“…global and local. The new intensity of a pixel is calculated based on global histogram equalization function with respect to the pixel values of neighborhood [4]. Shyu et al [5] suggested a genetic algorithm in which enhancement problem is formulated as an optimization problem.…”
Section: Introductionmentioning
confidence: 99%
“…Color histogram [29,30] represents the distribution of colors in an image. A color histogram is a stable object illustration which is unaffected by occlusion and changes in viewing conditions, and that a color histogram has the advantage of being insensitive to scaling, rotation, and small deformation of objects and being immune to noise [31].…”
Section: Color Histogram and Image Retrievalmentioning
confidence: 99%